PEMBELAJARAN BERDIFERENSIASI SEBAGAI MODUL AJAR PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA SMK - Musa, Anton; Dzakiyyuddin, Mohammad; Ali Nurzen Amin, Aang (Universitas Muhammadiyah Surakarta, 2023)
This research was conducted due to the policy of renewing the national curriculum to the Merdeka Belajar curriculum, which contains Differentiated Learning approach and the Project for Strengthening the Pancasila Student Profile (P5) for elementary to high school levels. The interesting thing to study here is how to implement this policy in the realm of vocational education at SMK (Vocational High School). This research aims to investigate how the differentiated learning approach is implemented on the Project for Strengthening the Pancasila Student Profile in vocational schools. This research uses a qualitative approach with descriptive analysis methods. Data collection uses observation, interviews, and documentation studies. Miles and Huberman's interactive analysis techniques are used in data analysis, including data reduction, display, and conclusion drawing. This research shows that planning involves analyzing school readiness, forming committees, establishing success indicators, providing P5 training for teachers, mapping students using diagnostic assessments, determining P5 themes, and designing learning modules. Implementation includes P5 socialization, differentiated learning processes, product guidance, and productive expo projects. Evaluation has been carried out through reflection sessions at the end of each lesson, performance rubrics, and written tests. In general, a differentiated learning approach as module for the Project for Strengthening the Profile of Pancasila Students in Vocational Schools has been implemented continuously and has had a positive impact on students, as shown by increased enthusiasm and satisfactory assessment results.